Programa educativo de las grabaciones de voz en el desarrollo de la pronunciación en inglés en estudiantes de quinto grado de secundaria en la Institución Educativa 6010120 las Malvinas, Punchana 2022 - Sandoval Macedo, Elizabeth (2025)
The quantitative study aimed to evaluate the effectiveness of the educational program based on voice recordings in improving English pronunciation among fifth year high school students at Educational Institution No. 6010120 Las Malvinas, Punchana, 2022. The research was evaluative in nature, using field, contemporary cross-sectional, univariate, and quasi-experimental designs. Likewise, the study used a pronunciation test as the data collection instrument. For data validation, the Mann-Whitney U statistical test was applied, with a reliability level of 0.05, which is acceptable. The study population consisted of 142 students, with a sample of 65 students — 35 in the experimental group and 30 in the control group. The results indicate that the experimental group performed better in pronunciation than the control group (14.76 > 11.28 on a vigesimal scale). The averages were also higher in the indicators: identification and production of sounds (14.63 > 11.37), stress (15.10 > 11.03), and intonation (15.25 > 10.96). The study concluded that the implementation of the educational program using voice recordings significantly improved English pronunciation (p-value = 0.025 < α = 0.05).